Pedagogía estética y vanguardias artísticas - Collelldemont Pujadas, Eulàlia (Revista Española de Pedagogía, 2018)
This study analyzes the contributions of the avant-garde movements in art to aesthetic pedagogy. To this end, an introduction is made firstly of the ideology on which its birth was based. Subsequently, a review is made of the pedagogic will and main innovations with regard to the educational relation. At the same time, a discussion is made of the pedagogic mechanisms assimilated by the avant-garde, and the fruits obtained.
Keywords: pensamiento pedagógico; España; Revista Española de Pedagogía